Instrumentation for digital nuclear spectroscopy : proceedings of the IAEA technical meeting held in Vienna, Austria, 11-15 October 2010 - IAEA Technical Meeting ( 2010: Vienna, Austria); International Atomic Energy Agency (Vienna : International Atomic Energy Agency, 2013)
Includes bibliographical references